Analysis of the Functioning of the Automatic Exchange of Information about Financial Accounts after Implementation of the Common Reporting Standard - Matras Tomasz (Analiza funkcjonowania automatycznej wymiany informacji finansowych po wdrożeniu wspólnego standardu sprawozdawczego (Common Reporting Standard), 2023)
The adoption of the Common Reporting Standard (CRS) by the OECD in 2014 raised many concerns. Banks were particularly obliged to implement many changes in order to properly collect and aggregate data on tax residence of their clients and correctly report them to the tax administration authorities. The aim of this article was to assess the functioning of the CRS, taking into account the benefits of implemented changes and critical voices regarding the functioning of the standard. The efficiency of the solution based on OECD data and a critical analysis of some aspects of the CRS were presented. The adopted research method was based on verification of official OECD documents and comparative analysis of data presented by the organization with the research conducted by scientific institutions and other private and public entities. According to the results of the research, the automatic exchange of financial information is not functioning optimally, and reforms need to be carried out. The additional revenues generated by the CRS are relatively low compared to the tax losses still generated by tax optimization.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2023; vol. 67, nr 1, s. 106-117
Keywords: Organisation for Economic Cooperation and Development; OECD; Common Reporting Standard; CRS; financial information; taxes; financial institutions; wymiana informacji finansowych; podatki; instytucje finansowe